Inactivation of the plasma membrane ATPase of Schizosaccharomyces pombe by hydrogen peroxide and by the Fenton reagent (Fe2+/H2O2): nonradical vs. radical-induced oxidation - Sigler, K; Gille, G; Vacata, V; Stadler, N; Höfer, M (Folia microbiologica, 1998)
In the absence of added Fe2+, the ATPase activity of isolated Schizosaccharomyces pombe plasma membranes (5-7 mumol P(i) per mg protein per min) is moderately inhibited by H2O2 in a concentration-dependent manner. Sizable inactivation occurs only at 50-80 mmol/L H2O2. The process, probably a direct oxidative action of H2O2 on the enzyme, is not induced by the indigenous membrane-bound iron (19.3 nmol/mg membrane protein), is not affected by the radical scavengers mannitol and Tris, and involves a decrease of both the K(m) of the enzyme for ATP and the V of ATP splitting. On exposing the membranes to the Fenton reagent (50 mumol/L Fe2+ + 20 mmol/L H2O2), which causes a fast production of HO. radicals, the ATPase is 50-60% inactivated and 90% of added Fe2+ is oxidized to Fe3+ within 1 min. The inactivation occurs only when Fe2+ is added before H2O2 and can thus bind to the membranes. The lack of effect of radical scavengers (mannitol, Tris) indicates that HO. radicals produced in the bulk phase play no role in inactivation. Blockage of the inactivation by the iron chelator deferrioxamine implies that the process requires the presence of Fe2+ ions bound to binding sites on the enzyme molecules. Added catalase, which competes with Fe2+ for H2O2, slows down the inactivation but in some cases increases its total extent, probably due to the formation of the superoxide radical that gives rise to delayed HO. production.
Keywords: železo; oxidace-redukce; Schizosaccharomyces; Cell Membrane; vztah mezi dávkou a účinkem léčiva; kinetika; peroxid vodíku; Oxidation-Reduction; volné radikály; Hydrogen Peroxide; adenosintrifosfatasy; Dose-Response Relationship, Drug; Iron; Kinetics; Free Radicals; Adenosine Triphosphatases; buněčná membrána